Victim-oriented approach in east-european criminal law: conceptual foundations for justice system transformation : preprint - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (My University, 2025)
This paper examines the victim-oriented approach in criminal law as a paradigmatic shift from punitive to restorative justice models. The study analyzes international standards including the UN Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power (1985) and the European Strategy on Victims' Rights (2020-2025). The author proposes conceptual foundations for transforming criminal justice systems by placing victims at the center of legal proceedings. The research presents a theoretical framework for a "Criminal Code for Victims" that prioritizes restitution, satisfaction, compensation, and rehabilitation over traditional punishment mechanisms. Key elements include expanded definitions of victimhood (primary, ricochet, and collective victims), comprehensive restoration mechanisms, and procedural guarantees for victim participation. The paper argues that effective criminal justice requires cultural transformation from state punitive instruments to healing and restoration mechanisms for those most in need of protection. У статті досліджується віктим-орієнтований підхід у кримінальному праві як парадигмальний зсув від каральної до відновної моделі правосуддя. Аналізуються міжнародні стандарти, включаючи Декларацію основних принципів правосуддя для жертв злочинів і зловживання владою ООН (1985) та Європейську стратегію з прав потерпілих (2020-2025). Автор пропонує концептуальні засади трансформації системи кримінального правосуддя шляхом розміщення жертв у центрі судового процесу. Дослідження представляє теоретичну модель "Кримінального кодексу для потерпілих", що пріоритизує реституцію, сатисфакцію, компенсацію та реабілітацію над традиційними каральними механізмами. Ключові елементи включають розширені визначення жертви (первісна, рикошетна та колективна жертви), комплексні механізми відновлення та процесуальні гарантії участі потерпілих. Стверджується, що ефективне кримінальне правосуддя потребує культурної трансформації від державних каральних інструментів до механізмів зцілення та відновлення для тих, хто найбільше потребує захисту.
Tuliakov V. O. Victim-oriented approach in east-european criminal law: conceptual foundations for justice system transformation / V. O. Tuliakov // (June 13, 2025). - 44 p. - preprint. - Режим доступу: Available at SSRN: https://ssrn.com/abstract=5292103 or http://dx.doi.org/10.2139/ssrn.5292103 ; https://hdl.handle.net/11300/29736
Keywords: victim-oriented approach; restorative justice; criminal law reform; victim rights; restitution; satisfaction; compensation; rehabilitation; international standards; justice transformation; Ukraine; Eastern Europe; Law drafting; віктим-орієнтований підхід; відновне правосуддя; реформа кримінального права; права жертв; реституція; сатисфакція; компенсація; реабілітація; міжнародні стандарти; трансформація правосуддя